Arms involvement and their impacts on player vertical jump volleyball tests performance - Zerf, Mohammed; Housseyn, Ameur; Kaddourbey, Belkheyr (Pedagogy and Psychology of Sport, 2025)
Objective The purpose of this study was to investigate how the use of arms affects the accuracy of vertical jump volleyball tests conducted in field settings. It was found that incorporating arm movements can increase vertical jump height by approximately 10% compared to jumps without using the arms. The study utilized the Standing Reach and Myotest accelerometric system to assess the impact of different arm protocols on vertical jump performance. The study also examined the relationship between arm involvement in vertical jump tests and performance in block and spike volleyball techniques, with and without a step at the start of the jump. Materials and Methods: We evaluated the performance of our top players in the national championship based on the following criteria: Standing Reach, Myotest system results, Vertical Jump Spike, and Vertical Jump Test with and without arm swings. Results: Our results validated Standing Reach as the most correlated test with technical volleyball tests when compared to the Myotest accelerometric system. Additionally, Standing Reach showed a significant correlation with Myotest in predicting the maximum athletic height in vertical jump. Conclusions: Based on the study design and protocol involving arm swings, we affirm that the movement of the arms is a crucial factor in assessing vertical jumps in technical or athletic volleyball tests. This study acknowledges the significance of arm swings in determining Standing Reach and their correlation with player performance in the Spike or Block test. Conversely, the study highlights the lack of correlation between arm swings and player performance as measured by the Myotest accelerometric system in the arms protocol. This study underscores the importance of addressing this protocol issue for the accurate assessment of vertical jumps in volleyball tests using the Myotest system.